THE MAIN ADVANTAGES OF CONTROLLING THE KEYBOARD WITH TEN - FINGER TOUCH METHOD - MADLOVA, Iva (Journal of Technology and Information Education, 2012)
This contribution deals with the control of a computer keyboard with ten-finger touch method. It offers several definitions of defining this method and approach events that preceded its official recognition. In the final stage explores the main advantages that brings users control the keyboard through ten-finger touch methods.
Keywords: keyboarding; ten-finger touch method; typing blindly